Static MLC transmission simulation using two‐dimensional ray tracing. Issue 8 (20th May 2022) - Adam, David P.; Bednarz, Bryan P.; Frigo, Sean P.
Abstract: Purpose: We investigated the hypothesis that the transmission function of rounded end linearly traveling multileaf collimators (MLCs) is constant with position. This assumption is made by some MLC models used in clinical treatment planning systems (TPSs) and in the Varian MLC calibration convention. If not constant, this would have implications for treatment plan QA results. Methods: A two‐dimensional ray‐tracing tool to generate transmission curves as a function of leaf position was created and validated. The curves for clinically available leaf tip positions (−20 to 20 cm) were analyzed to determine the location of the beam edge (half‐attenuation X‐ray [XR]) location, the beam edge broadening (BEB, 80%–20% width), as well as the leaf tip zone width. More generalized scenarios were then simulated to elucidate trends as a function of leaf tip radius. Results: In the analysis of the Varian high‐definition MLC, two regions were identified: a quasi‐static inner region centered about central axis (CAX), and an outer one, in which large deviations were observed. A phenomenon was identified where the half‐attenuation ray position, relative to that of the tip or tangential ray, increases dramatically at definitive points from CAX. Similar behavior is seen for BEB. An analysis shows that as the leaf radius parameter value is made smaller, the size of the quasi‐static region is greater (and vice versa). Conclusion: The MLC transmission curve properties determined by this study have implications both for MLC position calibrations and modeling within TPSs. Two‐dimensional ray tracing can be utilized to identify where simple behaviors hold, and where they deviate. These results can help clinical physicists engage with vendors to improve MLC models, subsequent fluence calculations, and hence dose calculation accuracy.